2022
DOI: 10.1021/acsanm.1c04320
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution R2R-Compatible Printing of Carbon Nanotube Conductive Patterns Enabled by Cellulose Nanocrystals

Abstract: Carbon nanotubes (CNTs) with enhanced properties compared to conventional materials are a leading material of choice for fabricating next-generation electronic devices. Nanocellulose-based conductive component-enabled electronics also offer great potential for commercial scalability of environmentally friendly, sustainable, flexible, wearable electronics. Printing these functional materials through R2R printing will enable the economic and high-throughput production of next-generation electronic devices. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The length of nanofibers varies and can reach 5 µm. Enlarged images show that SWCNTs tend to curl, which can lead to the appearance of large agglomerates in liquid dispersions [44].…”
Section: Sem Studymentioning
confidence: 99%
“…The length of nanofibers varies and can reach 5 µm. Enlarged images show that SWCNTs tend to curl, which can lead to the appearance of large agglomerates in liquid dispersions [44].…”
Section: Sem Studymentioning
confidence: 99%
“…7 Viscous solution (V.S.). 8 Artificial seawater (A.SW.). 9 Beverages include wine, juice, milk, tea, and others.…”
Section: Laminated Electrodesmentioning
confidence: 99%
“…However, the fundamental challenges lie in transferring the lab-scale fabrication techniques to high-throughput industrial-scale manufacturing when the products go to mass production [4]. Roll-to-roll (R2R) fabrication processes were improvised for their simplicity with lower capital equipment expenses [5][6][7][8], higher throughputs [9], and a cost-effective alternative for printing lab-on-a-chip (LoC) devices [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the speed at which the ink can be dragged is currently limited to below 3 mm min −1 due to insufficient wetting contrast between the land and the cells. [31,[34][35][36] By controlling the substrate surface chemistry to create hydrophilic/hydrophobic patterns, higher wetting contrast can be achieved, enabling high-speed ink printing. [27,29] Fluid dynamics simulations have shown that the most favorable configuration for achieving high-speed ink filling, while ensuring the liquid fills the cell with no trapped air, is to create cells with all recessed surfaces being hydrophilic surrounded by a hydrophobic land.…”
Section: Introductionmentioning
confidence: 99%
“…However, the speed at which the ink can be dragged is currently limited to below 3 mm min −1 due to insufficient wetting contrast between the land and the cells. [ 31,34–36 ] By controlling the substrate surface chemistry to create hydrophilic/hydrophobic patterns, higher wetting contrast can be achieved, enabling high‐speed ink printing. [ 27,29 ]…”
Section: Introductionmentioning
confidence: 99%